Small-scale Aquaponics and Hydroponics Systems: Pak Choy and Spinach Growth Rate Comparison - Lynn, Lee Yee; Mohd Amin, Nor Amira; Arif, Mohd Afzanizan; Ibrahim, Rabizah; Mohd Ismail, Nurul Izzati (Multidisciplinary Applied Research and Innovation, 2022)
Kelantan International Organic Research Centre (KORC) used small-scale aquaponic and hydroponic systems to test their suitability for dwarf Pak Choy and spinach planting. For the KORC, the conventional soil planting method is often ineffective due to monkey attacks and high temperatures on open farming. This research will test the efficacy of Kelantan Biotech Corporation (KBC) Sdn Bhd's own product, BioHijja Effective Microbe (EM) solution in hydroponics planting. Aquaponics and hydroponics systems using were used to grow dwarf Pak Choy and spinach. To compare the quality of Grabbit seeds sold by KBC to other brands, the germination time and yield of both brands were observed. To compare the efficiency of aquaponics and hydroponics planting methods, the height and number of leaves of plants were measured after 7 days. Compared to other brands, Grabbit had lower seed quality dwarf Pak Choy and higher seed quality spinach. Moreover, the BioHijja EM hydroponics system outperformed the aquaponics system in terms of plant height difference around 0.7cm and 5 news leaf for Grabbit and JC Garden Pak Choy, respectively. As a result, other brands of dwarf Pak Choy seeds could be surveyed to replace the low seed quality supply from the Grabbit brand at KBC. However, using bio-pesticides along with relocating the project base to an area with better air circulation should be considered to improve the accuracy of future findings.